The taxonomy of Amycolatopsis lurida TRM64739 and Bacillus haynesii - Liu, Zhan-wen; Luo, Xin-rong; Xia, Zhan-feng; Wan, Chuan-xing; Zhang, Li-li (Frontiers in Microbiology, 2025)
IntroductionActinomycetes are a significant source of natural products. Amycolatopsis, a rare actinomycete, is particularly noted for its robust potential in secondary metabolite production, but most of the biosynthetic gene clusters (BGCs) are silent. To discover new BGCs and their metabolites, this study employed genome mining and co-culture techniques to explore the secondary metabolites produced by Amycolatopsis lurida TRM64739.MethodA novel BGC was identified in A.lurida TRM64739 using antiSMASH and phylogenetic analysis, this new BGC was activated through co-culturing A. lurida TRM64739 with Bacillus haynesii. Subsequently, a series of phenazine compounds were isolated and identified by chromatographic separation, such as silica gel column (100-200 mesh), Sephadex LH-20 and HPLC, and spectral analysis, such as NMR and UPLC-HRESI-MS/MS, respectively.ResultsFive phenazine compounds were isolated and identified as compound 1(1,6-Dimethoxyphenazine), compound 2(1,6-Dihydroxyphenazine), compound 3(phenazine-1-carboxylic acid), compound 4(6-hydroxy-1-methoxyphenazine), and compound 5(1,6-p-chlorophenylphenazine). Among these, compounds1-4 are known, while compound 5(1,6-p-chlorophenylphenazine) represents a new compound and has exhibited antimicrobial activity to clinically drug-resistant strains (A. baumannii ATCC19606, P. aeruginosa ATCC27853) and plant pathogenic bacteria (E. amylovora ATCC BAA-2158).DiscussionOur work also demonstrates that the combined approach of genome mining and activation of silent BGCs is a useful method for the discovery of new natural products.